1991
DOI: 10.1088/0953-8984/3/26/018
|View full text |Cite
|
Sign up to set email alerts
|

Mossbauer and AC-susceptibility investigations of the alloy series FeAl1-xMnx

Abstract: Mossbauer and Ac-susceptibility measurementshave been carriedout on the alloy series FeAl,_,Mn, within the range 0.05 S x b 0.40. M6ssbauer spectra reveal the presence of electron charge density and magnetic hypefine field (BM) distributions at two iron sites. Thecharge density rises linearly with Mn concentration while B,,increases non-linearly with x indicating a polarized spin density of the itinerant electrons at the Fe nucleus due to the near neighbouring Fe and Mn magnetic moments. The onset of magnetism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 34 publications
1
14
0
Order By: Relevance
“…Theoretical calculations [2] based on a diluted and random-bond Ising model interpret this anomaly as due to a spin-glass (SG) behaviour. This hypothesis was experimentally confirmed by Kobeissi [3] who reported that the alloy with x ¼ 0.40 in the Fe 0.50 (Al 1--x Mn x ) 0.5 system presents a SG to P phase transition. By using both Mö ssbauer and magnetization techniques Pé rez Alcá zar et al [4] proved the presence of a reentrant spin-glass (RSG) phase in the Fe 0.45 Mn 0.30 Al 0.25 alloy.…”
mentioning
confidence: 59%
See 1 more Smart Citation
“…Theoretical calculations [2] based on a diluted and random-bond Ising model interpret this anomaly as due to a spin-glass (SG) behaviour. This hypothesis was experimentally confirmed by Kobeissi [3] who reported that the alloy with x ¼ 0.40 in the Fe 0.50 (Al 1--x Mn x ) 0.5 system presents a SG to P phase transition. By using both Mö ssbauer and magnetization techniques Pé rez Alcá zar et al [4] proved the presence of a reentrant spin-glass (RSG) phase in the Fe 0.45 Mn 0.30 Al 0.25 alloy.…”
mentioning
confidence: 59%
“…Introduction Cast Fe-Mn-Al alloys in the bcc disordered phase have been highly studied from the theoretical and experimental point of view, due to the different magnetic phases that can appear as a consequence of the variation in composition and in temperature [1][2][3][4][5][6][7]. A preliminary work [1], performed at room temperature (RT), showed that the ferromagnetic (F) character of the alloys changes to a paramagnetic (P) one when the Al or Mn concentration increases.…”
mentioning
confidence: 99%
“…These alloys are usually prepared according to the Chakrabarti method [44]. In the BCC structural phase, magnetic phases such us paramagnetic (P), ferromagnetic (F), antiferromagnetic (AF), spin-glass (SG) and reentrant spinglass (RSG) in the F and AF phases [45][46][47], respectively, were detected. Recently the pure and reentrant superparamagnetic (SP) phases were experimentally postulated [48,49] in this ternary Fe-Mn-Al system and a large effort is now in progress to understand this behavior.…”
Section: Introductionmentioning
confidence: 99%
“…These alloys have been generally prepared following the Chakrabarti method [1]. In the BCC structural phase the magnetic phase diagram presents behaviours like paramagnetic (P), ferromagnetic (F), antiferromagnetic (AF), spin-glass (SG) and reentrant spin-glass (RSG) in the F and AF phases [2][3][4], depending on both the concentration and the temperature. Recently, the pure and reentrant superparamagnetic (SP) phases were experimentally observed [5,6] in this alloy system.…”
Section: Introductionmentioning
confidence: 99%